P140 Kylie, Jason, Chantelle and Jess: creating characters as a catalyst for change. Enabling the community to understand and meet the needs of young people experiencing loss and bereavement. (1st October 2013) - Archer, Nikki; Coleman, Jenni; Rodgers, Carol; Chetwynd, Helen
Abstract : A collaborative project between St Giles Hospice and Lichfield District Safer Community Partnership was undertaken which aimed to build sustained confidence and capacity of community staff to enable them to help and support young people who are coping with loss and bereavement. For children and young people within our local community to be better supported and understood through their loss experiences There is strong evidence that bereavement and the changes that accompany it can make children and young people vulnerable to poor outcomes, particularly in disadvantaged circumstances. Many children and young people are able to accommodate and adjust to their loss if they receive the right help and support through their usual networks, however, those who work with young people tell us they feel ill equipped to support young people who have experienced loss and bereavement. During a half day workshop participants were afforded an opportunity to explore death, dying, bereavement and loss through the creation of a character based within their own experiences. Pre and post workshop participants were asked to rate how confident they felt talking to young people about death and dying? supporting a young person who has been bereaved? The results were very positive: 58 attended 94% assessed themselves with a higher post workshop score, the average score increased from 5 to 8 for both questions. All valuedthe workshop. A follow up focus group was held 9 months after the initial workshop. Feedback demonstrated the ripple effect the workshop had ona personal and professional level. There was evidence that the increased confidence had been sustained. This project demonstrates how the hospice is engaging with it's local community to build capacity and better equip everyone in supporting young people experiencing loss and bereavement.